Arabidopsis Ca2+-dependent nuclease AtCaN2 plays a negative role in plant responses to salt stress. (April 2019) - Sui, Wenting; Guo, Kunyuan; Li, Li; Liu, Shenkui; Takano, Tetsuo; Zhang, Xinxin
Highlights: AtCaN2 showed a dual endonuclease and exonuclease activity. AtCaN2 was strongly induced in senescent siliques and by salt stress. A mutation in the AtCaN2 gene improved plant tolerance to salt stress. A mutation in the AtCaN2 gene decreased H2 O2 accumulation and ROS-induced PCD during salt stress. A mutation in the AtCaN2 gene increased the expression of genes encoding ROS-scavenging enzymes during salt stress. Abstract: Eukaryotic nucleases are involved in processes such as DNA restriction digestion, repair, recombination, transposition, and programmed cell death (PCD). Studies on the role of nucleases have mostly focused on PCD during plant development, while the information on nucleases involved in responses to different abiotic stress conditions remains limited. Here, we identified a Ca 2+ -dependent nuclease, AtCaN2, in Arabidopsis thaliana and characterized its activity, expression patterns, and involvement in plant responses to salt stress. AtCaN2 showed a dual endonuclease and exonuclease activity, being able to degrade circular plasmids, RNA, single-stranded DNA, and double-stranded DNA. Expression analysis showed that AtCaN2 was strongly induced in senescent siliques and by salt stress. Overexpression of AtCaN2 decreased the plant tolerance to salt stress conditions, leading to an excessive H2 O2 accumulation. However, an atcan2 mutant showed better tolerance to salt stress and a lower level of H2 O2 accumulation. Moreover, the expression of several genes (AtAPX1, AtGPX8, and AtSOD1), encoding reactive oxygen species-scavenging enzymes (ascorbate peroxidase 1, glutathione peroxidase 8, and superoxide dismutase 1, respectively), was highly induced in the atcan2 mutant under salt stress conditions. In addition, salt-stress-induced cell death was increased in the AtCaN2 -overexpressing transgenic plant but decreased in the atcan2 mutant. On the basis of these findings, we conclude that AtCaN2 plays a negative role in plant tolerance to salt stress. A AtCaN2 knock out could reduce ROS accumulation, decrease ROS-induced PCD, and improve overall plant tolerance.